Effect of nitrogen on high temperature oxidation behavior of AlN-doped gradient coating. (1st May 2022) - Yang, Yingfei; Xiao, Qin; Yang, Lanlan; Ren, Pan; Li, Wei; Zhu, Shenglong; Wang, Fuhui
Abstract: Three nitrides-doped gradient coatings were manufactured by reactive magnetron sputtering. The influence of nitrides on the oxidation performance was discussed. As the nitrides content increased, the weight gain of NiCrAlYHfSi, GC1, GC2 and GC3 coatings reached 0.306, 0.333, 0.463 and 0.979 mg/cm 2 after 24 h of oxidation. It was found that the present of nitrides could inhibit the θ→α transition of Al2 O3, and increased the oxidation rate of coatings but the residual stress in oxide scale is reduced accordingly. Excessive doping of nitrides is detrimental to coatings, a proper doping amount is critical to the performance of coating. Highlights: Three types of nitrides-doped gradient coatings were manufactured to study the influence of nitrides on oxidation. Doping nitrides accelerate the oxidation rate of coatings, both in transient and steady oxidation stages. The nitrogen atoms enter the oxygen vacancies in θ-Al2 O3 to form Al-N bonds, which inhibit the θ→α transition of Al2 O3 . The oxidation of AlN would form porous Al2O3, resulting in a high oxidation rate of doped coatings. Excessive doping of nitrides will cause nitrogen ions diffusing into superalloys and form nitrides.